2021
DOI: 10.21203/rs.3.rs-194877/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Machine Learning Framework that Integrates Multi-omics Data Predicts Cancer-related LncRNAs

Abstract: Background: LncRNAs (Long non-coding RNAs) are a type of non-coding RNA molecule with transcript length longer than 200 nucleotides. LncRNA has been novel candidate biomarkers in cancer diagnosis and prognosis. However, it is difficult to discover the true association mechanism between lncRNAs and complex diseases. The unprecedented enrichment of multi-omics data and the rapid development of machine learning technology provide us with the opportunity to design a machine learning framework to study the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…By following a complex combination of (similarity) clustering, Yuan et al, identified previously unrecognized non-coding long RNAs (lncRNAs) in gastric cancers [ 149 ]. In parallel, Li et al, compared several classification/regression models to identify novel lncRNAs in GEA [ 150 ].…”
Section: Machine Learning—basic Concepts Specific Applications and Future Directions In Geamentioning
confidence: 99%
“…By following a complex combination of (similarity) clustering, Yuan et al, identified previously unrecognized non-coding long RNAs (lncRNAs) in gastric cancers [ 149 ]. In parallel, Li et al, compared several classification/regression models to identify novel lncRNAs in GEA [ 150 ].…”
Section: Machine Learning—basic Concepts Specific Applications and Future Directions In Geamentioning
confidence: 99%